Construction Of A Computerised Information-Processing Test Battery - Johann M. Schepers (SA Journal of Industrial Psychology, 2002)
The primary goal of the study was to construct a computerised information-processing test battery to measure choice reaction time for up to and including six bits of information, to measure discrimination reaction time with regard to colour patterns and form patterns, to measure rate of information processing with regard to perceptual stimuli and conceptual reasoning, and to develop a suitable scoring system for the respective tests. The battery of tests was applied to 58 pilots. Opsomming Die hoofdoel van die studie was om ‘n gerekenariseerde inligtingverwerkingstoets-battery te konstrueer om keusereaksietyd tot en met ses bis inligting te meet, om diskriminasie-reaksietyd ten opsigte van kleurpatrone en vormpatrone te meet, om tempo van inligtingverwerking ten opsigte van perseptuele stimuli en konseptuele redenering te meet en om ‘n gepaste nasienstelsel vir die onderskeie toetse te ontwikkel. Die battery toetse is op 58 vlieëniers toegepas